A Linguistic Comparison of Fe/male translations of Mosteghanemi’s Novel Dhakirat Al-Jasad (1998 - BELMOKHTAR, Kheira (My University, 2019)
Translating Novels into English poses a challenge for translators because languages represent different cultural systems. Translators may not be aware about the gender system as part of the target language. In this light, this study examines the translations of Mosteghanemi’s novel Dhakirat Al-Jasad by a male and a female authors. The study investigates the influence of fe/male translators on linguistic choices, and whether they have employed feminist translation strategies. Using Lakoff’s model and feminist translation strategies, the analysis reveals that gender might have an effect on the translated text : the male translator uses feminist translation strategies and avoids sexism. However, the female translator employs more feminist strategies, supplementing wherever women were devalued in the original text. Other variables may also have influenced the translators’ choices such as their cultural background, native language, and the literal/ free translation strategies employed by Sreih/ Cohen respectively. To investigate the role of the translator’s gender on the translated texts, a larger sample is needed for future research.
Keywords: Culture, Gender, Literary translation, Lakoff’s Model, Feminist Translation Strategies